A Critical Review of "Non-Existence of God" on the Aristotle's Book “Nicomachean Ethics” and its Effect on Philosophical Ethics Writing among Muslims - Zahra Atashi; Mojtaba Javidi; Alireza Farsinejad (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Aristotle “Nicomachean's” book on ethics is one of his most important books on ethics. By meditating on this book, one becomes the guardian of God, in which there are no traces of the many letters of God, one of the divine religions. Given that God and man's relationship with him are the ruling spirit of all the teachings of the divine religions, and in particular the religion of Islam, and that Muslim ethicists have followed Aristotle in their philosophical ethics and formulation, this absence of the one God has had some effects on philosophical ethics. This article deals with this issue with a descriptive-analytical-critical method and has listed some of the consequences and results of formulating philosophical ethics based on Aristotle's ethics as follows: changing the subject and purpose of ethics, not considering a place for slavery and relationship ethics between Man and God, the absence of the concept of the hereafter and eternal life in the science of ethics, different views on the concepts of goodness, happiness, and virtue in Islam, lack of explanation of the place of narration, revelation, and law in Islamic ethics and separation of ethics from revelatory sciences such as jurisprudence, personalization of Islamic ethics and lack of attention to its social dimensions.